2005
DOI: 10.1007/s00125-005-1691-9
|View full text |Cite
|
Sign up to set email alerts
|

IA-2 antibody prevalence and risk assessment of early insulin requirement in subjects presenting with type 2 diabetes (UKPDS 71)

Abstract: Aims/hypothesis: Established autoimmune markers of type 1 diabetes, including islet cell autoantibodies (ICA) and autoantibodies to glutamic acid decarboxylase (GADA) have been used to screen people presenting with type 2 diabetes for latent autoimmune diabetes in adults. We have examined the prevalence of autoantibodies to protein tyrosine phosphatase isoforms IA-2 (IA-2A) and IA-2β/phogrin (IA-2βA) in a cohort of adult UKPDS patients thought to have type 2 diabetes, and investigated the possible role of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 25 publications
5
53
1
1
Order By: Relevance
“…The difference in the proportion of GADA-positive patients requiring insulin by 6 years in this study (73%) compared with those previously reported for UKPDS LADA (33 and 38%) [7,22] could be due to differences in ascertainment by antibody assays of variable sensitivities [23].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The difference in the proportion of GADA-positive patients requiring insulin by 6 years in this study (73%) compared with those previously reported for UKPDS LADA (33 and 38%) [7,22] could be due to differences in ascertainment by antibody assays of variable sensitivities [23].…”
Section: Discussioncontrasting
confidence: 68%
“…Although GADA levels at diagnosis can help to predict the need for insulin therapy within the next 6 years [7,22] subsequent GADA measurements and fluctuations in levels are not indicators of disease progression or therapy requirement. Genetic and autoimmune markers in LADA indicate a similar aetiology to juvenile-onset diabetes [5,23,34,35] but these markers do not provide important aids to clinical management of LADA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IA-2A concentration was highest among patients with the HLA-DQB1 *0302/X genotype. IA-2A are known to be associated with a rapid onset of type 1 diabetes as well as with young age at onset [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…GADA were measured by a radioligand binding assay, based on human 35 S-labeled recombinant GAD 65 [15]. The results are presented as an index: GADA index=100 * (un)/(p-n), where u is CPM (mean activity of all four measurements for a sample) of the unknown sample, n is CPM of the negative control, and p is CPM of the positive control.…”
Section: Gad 65-glutamic Acid Decarboxylase Antibodies (Gada)mentioning
confidence: 99%
“…Most of these studies assessed patients attending a single diabetes clinic and few of them evaluated the correlation between the presence of GADA and the clinical features of affected patients. While GADA is recognized as the marker with the highest sensitivity for LADA, fewer data are available on IA-2A in adult-onset diabetes (25), while IAAs are unlikely to be useful since they are a feature of childhood diabetes (26).…”
Section: Introductionmentioning
confidence: 99%